LINC00565 promotes the progression of colorectal cancer by upregulating EZH2 - Shao, Xiaxia (Oncol Lett, 2021)
The present study aimed to illustrate the role of LINC00565 in aggravating colorectal cancer (CRC) by targeting enhancer of zeste homolog 2 (EZH2). The relative levels of LINC00565 and EZH2 in CRC tissues, based on their Tumor-Node-Metastasis stage and tumor size, were detected by reverse transcription-quantitative polymerase chain reaction. The diagnostic value of LINC00565 in CRC was assessed by depicting receiver operating characteristic curves. Pearson's correlation test was applied to analyze the expression correlation between LINC00565 and EZH2 in CRC tissues. The transfection efficacy of three LINC00565 small interfering RNAs was examined in CRC HCT116 and SW480 cell lines. After knockdown of LINC00565, the proliferative and migratory abilities of CRC cells were detected by Cell Counting Kit-8 and Transwell assays, respectively. The subcellular distribution of LINC00565 was analyzed, and the interaction between LINC00565 and EZH2 was determined by RNA immunoprecipitation. Finally, co-regulation of LINC00565 and EZH2 on CRC cell functions was explored by performing rescue experiments. Results showed that LINC00565 was upregulated in CRC tissues, especially in patients with stage III+IV and in those with large tumor sizes, suggesting its diagnostic value in CRC. EZH2 was also upregulated in CRC tissues, showing a positive correlation with LINC00565. LINC00565 was mainly expressed in the cytoplasm and was found to bind with EZH2. Validation was performed by overexpressing EZH2, which abolished the role of silenced LINC00565 in regulating proliferative and migratory abilities in CRC. Therefore, the upregulation of LINC00565 in CRC tissues was found to stimulate the aggravation of CRC by upregulating EZH2.